How Wearing a Social Justice Lens Can Support You, Your Clients, and the Larger Community: An Intersectionality Workshop With a Twist - Jay, Melissa; Brown, Jason (Canadian Journal of Counselling and Psychotherapy, 2021)
Counsellors may not comprehend fully the impact of their blind spots as a result of unconscious cultural encapsulation. The authors propose a self-reflective method by which counsellors can self-examine their assumptions about diversity and intersectionality. They invite readers to engage with the contents of this article to identify their blind spots, biases, and assumptions through self-reflective exercises. This article summarizes an intersectionality workshop with a twist that was offered by Melissa Jay, Jason Brown, and Rebecca Ward at the 2019 conference of the Canadian Counselling and Psychotherapy Association. The intention of the workshop was (a) to raise consciousness about systemic oppression, (b) to explore Collins’s (2018c) culturally responsive and socially just case conceptualization as the framework for the workshop, (c) to bring client intersectionality to life using four vignettes they created, (d) to reflect on client intersectionality and cultural identity, and (e) to propose a method by which counsellors can self-examine their assumptions about diversity and intersectionality, leading to more culturally competent counselling.